Electrodermal activity and subjective annoyance in speech recognition tasks with noise as stress indicators. - Peixoto Perini, Beatriz; Masullo, Massimiliano; Samelli, Alessandra Giannella (International Journal of Audiology, 2026)
Objectives: Noise can cause changes in the activity of the sympathetic nervous system (SNS), which can be monitored through electrodermal activity (EDA). Our aim was to investigate electrodermal activity and annoyance during speech recognition tasks with competitive noise. Design and Study Sample: Cross-sectional study with forty normal-hearing adults. The EDA was monitored during relaxation in silence and three recognition tasks with monosyllables, in silence and with competitive pink noise at 65 dBA and 75 dBA. After noise conditions, a subjective scale of annoyance was administered. Results: There were significant differences in the latency of the first EDA signal (p < 0.001), number of EDA peaks (p < 0.001) and percentage of correct answers in the speech recognition task (p < 0.001) when comparing the conditions with and without noise. Regarding the subjective scale, there was a significant difference between the two noise conditions, with higher annoyance scores for the condition with the highest noise level (p < 0.001). Conclusion: Our results suggest that the presence of competitive noise (and higher noise levels) negatively impacts the speech recognition task and increases EDA due to greater activation of the SNS, as well as more intense noise levels causing greater annoyance, possibly resulting from higher levels of stress and listening effort.